Peran Organizational Citizenship Behavior Dalam Meningkatkan Efektivitas Tim Kerja: Studi Dalam Konteks Organisasi Modern - Hasibuan, Santi; Pasaribu, Ramadan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Organizational Citizenship Behavior (OCB) refers to voluntary employee behavior not included in formal job descriptions but contributes positively to organizational performance. This study aims to examine the role of OCB in enhancing team effectiveness within modern organizational contexts. The study uses a literature review method of national and international journals published in the last decade. The findings indicate that OCB behaviors such as helping others, team loyalty, and active participation significantly improve teamwork, group cohesion, and collective productivity. This study provides important implications for HR management in fostering a collaborative and productive work culture.